2012
DOI: 10.1186/1750-9378-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a combined triple method to detect causative HPV in oral and oropharyngeal squamous cell carcinomas: p16 Immunohistochemistry, Consensus PCR HPV-DNA, and In Situ Hybridization

Abstract: BackgroundRecent emerging evidences identify Human Papillomavirus (HPV) related Head and Neck squamous cell carcinomas (HN-SCCs) as a separate subgroup among Head and Neck Cancers with different epidemiology, histopathological characteristics, therapeutic response to chemo-radiation treatment and clinical outcome. However, there is not a worldwide consensus on the methods to be used in clinical practice. The endpoint of this study was to demonstrate the reliability of a triple method which combines evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 45 publications
2
64
3
3
Order By: Relevance
“…The expression of p16 is not limited to HPV-positive tumors. The specificity of p16 in screening for HPV-positive tumors ranged from 79% to 93% in two different studies [18, 19]. Hence, including patients who had an in situ hybridization HPV positive tumor, rather than a p16 positive, decreased the heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of p16 is not limited to HPV-positive tumors. The specificity of p16 in screening for HPV-positive tumors ranged from 79% to 93% in two different studies [18, 19]. Hence, including patients who had an in situ hybridization HPV positive tumor, rather than a p16 positive, decreased the heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HPV DNA in head and neck tumors is not sufficient to establish whether the virus is transcriptionally active or is a mere passenger in the mucosal epithelium. Recent studies have reported that mRNA expression of HPV E6 and E7 oncogenes and/or p16 protein levels, defined as a surrogate marker of E7 expression, are optimal biomarkers to differentiate transcriptional active HPVs from transient HPV infections in the tumor tissues [9]. Ndiaye et al [6] in their meta-analysis observed that among DNA HPV-positive oropharyngeal cancer cases, the frequencies of E6/E7 mRNA and p16(INK4a) positivity were 86.9 and 86.7%, respectively.…”
Section: Epidemiologymentioning
confidence: 99%
“…The reliability of ISH and Consensus PCR was determined using Fleiss' intra-class correlation coefficient (ICCC) [47,48]. The Kappa coefficients were divided into categories as described by Landis and Kock [49].…”
Section: Reliabilitymentioning
confidence: 99%